PENGARUH PERBEDAAN KONSENTRASI KITOSAN SEBAGAI EDIBLE COATING TERHADAP SIFAT FISIK, KIMIA DAN MIKROBIOLOGI BUAH STROBERI - Karimullah, RB. Moh.; Handarini, Kejora (Universitas Islam Madura, 2024)
This research is about the application of edible coating chitosan with various concentrations on the quality of strawberry. The aim of this research was to determine the effect of using chitosan as edible coating on the physical, chemical and microbiological properties of strawberries stored at cold temperatures and determine the appropriate concentration for making edible coating solutions to maintain the physical, chemical and microbiological properties of strawberries. This research used experimental method was a CRD with one factor (chitosan concentration) with 4 levels (level 1 = 0%; level 2 = 1%; level 3 = 2%; and level 4 = 3%) which was applied to strawberries. The analysis carried out in this research were weight loss, water content, TSS, TPC and total mold. The data of physical and chemical property tests were analyzed statistically using ANOVA. If there was significantly different, continued by Tukey’s HSD test at 5% level. Based on the research results, it was concluded that the use of chitosan as an edible coating had an effect on chemical and microbiological properties but had no effect on the physical properties of strawberries stored at cold temperatures and coating of 3% chitosan on strawberries for 12 days of cold storage was able to inhibit weight loss (6,15%), to inhibit the decrease of water content (90,61%), to inhibit the increase of TSS (7,3 oBrix), to inhibit the increase of TPC (1,7 x 105 CFU/g) and to inhibit the increase of total mold (3,6 x 104 CFU/g) compared to lower chitosan concentrations.